2011
DOI: 10.1094/cm-2011-1223-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nitrogen Fertilization on Nutrient Removal by Corn Grain

Abstract: Nitrogen fertilization and nutrient removal are some of the greatest challenges associated with the production of bioethanol from corn grain in the United States. The project was conducted in Missouri from 2008 to 2009 in a silt loam soil to determine the effect of N fertilization on the nutrient removal by corn grain. Corn grain removed 31 to 201 kg N/ha, 10 to 102 kg K/ha, 3 to 20 kg P/ha, 0.6 to 11 kg Ca/ha, 0.7 to 2.7 kg Fe/ha, 0.045 kg Mn/ha, and 0.003 kg Cu/ha, depending on the N rate. Our results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Similar to total aboveground corn N uptake, grain N uptake increased linearly as fertilizer N increased (Table 2, Fig. 1), agreeing with the results of Halvorson et al (2006), Barbieri et al (2008), and Holou et al (2011). With each kg N ha −1 increase in fertilizer N applied, grain N uptake increased by 0.38 kg N ha −1 .…”
Section: Resultssupporting
confidence: 85%
“…Similar to total aboveground corn N uptake, grain N uptake increased linearly as fertilizer N increased (Table 2, Fig. 1), agreeing with the results of Halvorson et al (2006), Barbieri et al (2008), and Holou et al (2011). With each kg N ha −1 increase in fertilizer N applied, grain N uptake increased by 0.38 kg N ha −1 .…”
Section: Resultssupporting
confidence: 85%
“…Plant uptake of Cu increased as N rate increased in both Harare and Kiboko. This N rate effect on Cu uptake was also found by Holou et al ( 2011 ) in Benin. There may have been a link between the increase in S and Cu uptake as soil inorganic S has also been found to complex with Cu (Marschner 2011 ; Bindraban et al 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…The application of N increased P uptake, with the exception of a few hybrids in Embu. Feil et al ( 1992 ) and Holou et al ( 2011 ) also found that N fertilizer applications increased P uptake consistently in continuous maize cropping systems. The application of N fertilizer has been found to increase root branching, particularly closer to the surface where P levels are highest (Postma et al 2014 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Further, Malik et al (2012) elucidated that approximately 80-90% of applied mineral P becomes plant unavailable due to opposing soil conditions. Feil et al (1992) and Holou et al (2011) expounded that additional N application could consistently increase P uptake under a continuous corn cultivation system. The applied N fertilizer could proliferate root branching in surface portion where closer to higher P concentration (Postma et al 2014).…”
Section: Discussionmentioning
confidence: 99%